The effect of voluntary IFRS adoption by unlisted fi rms on earnings quality and the cost of debt: empirical evidence from Korea - Lee, Young Hwan; Kang, Sun A.; Cho, Sang Min (Journal of Business Economics and Management, 2015)
The present study empirically examines how voluntary International Financial Reporting Standards (IFRS) adoption influences the earnings quality and the cost of debt of unlisted firms in Korea. Since 2011, when the adoption of IFRS by listed firms became mandatory, more unlisted firms have adopted IFRS voluntarily, improving the transparency and reliability of their accounting information. Using the sample of unlisted firms with 3year study period of preand post-IFRS adoption, we examine whether IFRS voluntary adopters show both lower discretionary accruals and the cost of debt than those of non adopters, and whether both discretionary accruals and the cost of debt of voluntary adopters decrease after IFRS adoption. We employ the Heckman's two stage approach in order to avoid sample selection bias and cross sectional pooled OLS regression with or without clustering test. We complimentary report the results from firm-fixed effect panel model to generalise the results. The results show that firms which adopt IFRS have a higher earnings quality and a lower cost of debt that those which do not. These findings suggest that when unlisted firms issue bonds and borrow money, IFRS adoption contributes to decreasing the cost of debt.